(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of the present study was to evaluate the importance of neourethral covering using vascularized dorsal flap for preventing fistula in Tabularized incised plate (TIP) urethroplasty. The study included 52 children (aged 2-10 years) who had hypospadias repaired including 44 with distal and 8 with mid shaft hypospadias. In all children, a standard tabularized incised plate urethroplasty was followed by reconstruction of new surrounding urethral tissue. A longitudinal dartos flap was harvested from excessive dorsal preputial and penile hypospadiac skin and transposed to ventral side by a buttonhole maneuver. It was sutured to the glans wings and the neomeatus and to the corpora covernosa over the neo-urethra. Thus the new urethra was completely covered with well-vascularzed subcutaneous tissue. At a mean follow-up of 18 months, the result was successful with no fistula or urethral stenosis, except 2 of the mid penile hypospadias. All patients had good functional and cosmetic results with straight penis and vertical slit shaped meatus at the tip of the penis. The 2 patients developed tiny fistula, which were closed spontaneously after meatal dilatation. In conclusion, urethral covering should be part of TIP urethroplasty. A dorsal well-vascularized dartos flap, button holed ventrally is a good choice for preventing fistula for distal and mid shaft hypospadias.